2017
DOI: 10.1002/stem.2749
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA-1604 Orchestrates Neural Differentiation through the miR-200c/ZEB Axis

Abstract: Clarifying the regulatory mechanisms of embryonic stem cell (ESC) neural differentiation is helpful not only for understanding neural development but also for obtaining high-quality neural progenitor cells required by stem cell therapy of neurodegenerative diseases. Here, we found that long noncoding RNA 1604 (lncRNA-1604) was highly expressed in cytoplasm during neural differentiation, and knockdown of lncRNA-1604 significantly repressed neural differentiation of mouse ESCs both in vitro and in vivo. Bioinfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…For lncRNAs and mRNA, the RNA‐sequencing library generation, workflow, and data analysis were performed as previously described [18]. The small RNA sequencing including miRNAs was also performed.…”
Section: Methodsmentioning
confidence: 99%
“…For lncRNAs and mRNA, the RNA‐sequencing library generation, workflow, and data analysis were performed as previously described [18]. The small RNA sequencing including miRNAs was also performed.…”
Section: Methodsmentioning
confidence: 99%
“…Accumulation research have indicated that lncRNAs serve as miRNAs "sponges" to influence gene expression base on the ceRNA regulation theory. [18][19][20] lncRNA SNHG1 sponges miR-15b-5p triggers SIAH1 activation and further leads to α-synuclein aggregation and neurotoxicity. 21 Likewise, RAB3IP induces HOTAIR acts as a sponge of miR-126-5p aggravates the progression of PD.…”
mentioning
confidence: 99%
“…LncRNA-1604 deficiency inhibits ectoderm differentiation and decreases the expression of neural progenitor cell markers (Sox1,Nestin,Zfp521,Pax6,. Further luciferase and RIP assays demonstrate that lncRNA-1604 can interact and sponge miR-200c to suppress the expression of the core transcription factors ZEB1/2 and the subsequently neural differentiation (Weng et al, 2018).…”
Section: Lncrna In Neurogenesismentioning
confidence: 98%